Thermodynamic Study of a Mediterranean Cyclone with Tropical Characteristics in September 2020 - Sotirios T. Arsenis; Angelos I. Siozos; Panagiotis T. Nastos (Atmosphere)
This study examines the evolution, structure, and dynamic and thermodynamic mechanisms of a Mediterranean tropical-like cyclone (TLC), or medicane (from Mediterranean–Hurricane), that occurred in the central Mediterranean region from 15 to 19 September 2020. This event is considered an extreme meteorological phenomenon, particularly impacting the Greek area and affecting the country’s economic and social structures. It is one of the most significant recorded Mediterranean cyclone phenomena in the broader Mediterranean region. The synoptic and dynamic environment, as well as the thermodynamic structure of this atmospheric disturbance, were analyzed using thermodynamic parameters. The system’s development can be described through three distinct phases, characterized by its symmetrical structure and warm core, as illustrated in the phase space diagrams and further supported by dynamical analysis. During the first phase, on 15 September, the structure of the upper tropospheric layers began to strengthen the parent barometric low, which had been in the Sirte Bay region since 13 September. The influence of upper-level dynamical processes was responsible for the reconstruction of the weakened barometric low. In the second phase, during the formation of the Mediterranean cyclone, low-level diabatic processes determined the evolution of the surface cyclone without significant support from upper-tropospheric baroclinic processes. Therefore, in this phase, the system is characterized as barotropic. In the third phase, the system remained barotropic but showed a continuous weakening tendency as the sea surface pressure steadily increased. This comprehensive analysis highlights the intricate processes involved in the development and evolution of Mediterranean cyclones with tropical characteristics.